2021
DOI: 10.1371/journal.pone.0255969
|View full text |Cite
|
Sign up to set email alerts
|

Properties of peptides released from salmon and carp via simulated human-like gastrointestinal digestion described applying quantitative parameters

Abstract: Apart from the classical (experimental) methods, biologically active peptides can be studied via bioinformatics approach, also known as in silico analysis. This study aimed to verify the following research hypothesis: ACE inhibitors and antioxidant peptides can be released from salmon and carp proteins during simulated in silico human-like gastrointestinal digestion. The potential to release biopeptides was evaluated using the BIOPEP-UWM quantitative criteria including the profile of biological activity, frequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 83 publications
(115 reference statements)
0
8
0
Order By: Relevance
“…It focuses on the kinetics of identifying if a molecule will reach its target protein in the body and how long it will remain in a bloodstream. Consequently, this technology may be used to analyze peptides, which can then be employed as components of functional foods or supplements (Borawska‐Dziadkiewicz et al., 2021). A number of in silico tools are available to assess ADMET properties of peptides comprising admetSAR (http://lmmd.ecust.edu.cn/admetsar1/), ADMETlab platform (http://admet.scbdd.com/), iDrug (https://drug.ai.tencent.com/cn), SwissADME (http://www.swissadme.ch), and so forth.…”
Section: Bioavailability Of Food Bapsmentioning
confidence: 99%
See 2 more Smart Citations
“…It focuses on the kinetics of identifying if a molecule will reach its target protein in the body and how long it will remain in a bloodstream. Consequently, this technology may be used to analyze peptides, which can then be employed as components of functional foods or supplements (Borawska‐Dziadkiewicz et al., 2021). A number of in silico tools are available to assess ADMET properties of peptides comprising admetSAR (http://lmmd.ecust.edu.cn/admetsar1/), ADMETlab platform (http://admet.scbdd.com/), iDrug (https://drug.ai.tencent.com/cn), SwissADME (http://www.swissadme.ch), and so forth.…”
Section: Bioavailability Of Food Bapsmentioning
confidence: 99%
“…The ADMET prediction findings indicated that these predicted peptides could be utilized as orally ACE‐inhibitory peptides. Furthermore, the ADMET lab platform tested peptides produced from salmon and carp using a simulated human‐like GID for bioactivity, safety, and drug‐like qualities (Borawska‐Dziadkiewicz et al., 2021). Human intestinal absorption was anticipated to range from 0.244 to 0.68.…”
Section: Bioavailability Of Food Bapsmentioning
confidence: 99%
See 1 more Smart Citation
“…Assessment of these specific properties, namely ADMET (absorption, distribution, metabolism, excretion, toxicity) for food peptides is therefore essential in their initial stage of identification as a biomolecule. This approach of predicting the druglikeness of the molecule based on ADMET has recently become a mandatory step in the in silico design of pro-health agents from food [37][38][39][40][41]. In the research process for the identification of bioactive peptides from food, ADMET is an important parameter due to the possible modification of their properties, which are difficult to assess by in vitro or in vivo methods.…”
Section: Admet Predictionmentioning
confidence: 99%
“…In recent years, the traditional preparation methods of antioxidant peptides have been well developed. In order to further optimize the preparation of antioxidant peptides to generate peptides with desired function and purpose, some bioinformat-ics have been applied to the research of antioxidant peptides (Chiozzi et al, 2016;Jara et al, 2018;Borawska-Dziadkiewicz et al, 2021). The acquisition of purposeful antioxidant peptides from different biological resources is increasingly becoming the driving force of the oil industry (Tadesse and Emire, 2020).…”
Section: Introductionmentioning
confidence: 99%